Kisah Dzulqarnain dalam Perspektif Sejarah Ilmu Tafsir - Hermansyah Hermansyah (STID DI AL-HIKMAH, 2016)
Dhu'l-Qarnayn figure immortalized in the Qur'an as an exemplary tale. Iaadalah figure righteous king who God anugrahkan powers and abilities to him so he can subdue the lands and invite people to believe in Allah, and in particular to protect a people to build a solid wall between them and Gog and Magog which is the who made mischief in the land. But all the pleasure that God has given him no cause he boasted that he attributed it all to God, therefore he warned that there's doomsday where everything will be destroyed and perish.